Edukasi Pembuatan Nugget Ikan Lele sebagai Alternatif Usaha untuk Meningkatkan Pendapatan UMKM D'pore Meme Situbondo - Andina Mayangsari; Kawakibi Ahmad Fadhil Mikala; Ahmad Mufid (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Catfish is a fish that is familiar to the community and has high nutritional value. FPST catfish biofloc pond is a practice area for entrepreneurship learning for students with the harvest directly marketed to catfish collectors. Dpore Meme Micro Business is one of the MSMEs in Situbondo that is engaged in the business of processing fish products into shredded fish and chili sauce. The problem faced by Dpore meme MSMEs currently is the need for diversification of superior products so that it can attract more consumers in the future. With the unprocessed catfish harvest to increase its added value, FPST collaborates with Dpore Meme MSMEs to process it into a product that will later become a new product from Dpore Meme MSMEs. The service method is carried out through counseling and accompanied by the practice of making catfish nuggets, packaging and branding. The results obtained from this service increase the knowledge and skills of processing catfish into catfish nuggets. It is hoped that this service can increase the knowledge and skills of Dpore meme MSMEs in processing catfish as well as becoming a new product for product diversification in its MSME.